THE ADJUVANT USE OF HERBAL MEDICINES TO AID BODY FAT LOSS IN OVERWEIGHT INDIVIDUALS - Zuccatti Ferracioli, Giulia; Angélica do Carmo, Nicolle; Maria Prates Saturnino, Laura; Luiza Felipe de Jesus, Ana; Paula Landi Librandi, Ana; Pereira Nobrega, Mariana; Peixoto Vianna, Marina; Cristina Paiva, Kelli (Health and Society, 2023)
Obesity is an emerging issue in Brazil and in the world since there are several pathologies associated with excessive weight. The use of medicinal plants is atemporal and they have been used as a source of food and for therapeutic purposes. Objective: The purpose of this study is to approach the possibility of herbal medicine in obese patients and to conceive through clinical studies and analysis the activity of Camellia sinensis (green tea) and Garcinia cambogia plants in cooperation for the reduction of body fat. Methods: The bibliographic survey considered original articles and reviews published between 2013 and 2021 in online databases, with studies in humans. Results: Forty-seven articles were pre-selected, and those were 30 papers discarded after analysis and the other 17 were submitted for reading on their respective themes. Conclusion: In the midst of these conceptions, it is concluded that there is a need for investment in research in the field of alternative medicine and herbal medicine in order to that these drugs be used efficiently and safely, since the clinical tests showed satisfactory results.